2018
DOI: 10.1016/j.jcp.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

A zonal Galerkin-free POD model for incompressible flows

Abstract: A domain decomposition method which couples a high and a low-fidelity model is proposed to reduce the computational cost of a flow simulation. This approach requires to solve the high-fidelity model in a small portion of the computational domain while the external field is described by a Galerkin-free Proper Orthogonal Decomposition (POD) model. We propose an error indicator to determine the extent of the interior domain and to perform an optimal coupling between the two models. This zonal approach can be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…In this work, to address the above problems, we used a Galerkin‐free method to construct the POD‐ROM for flow in fractured porous media. The Galerkin‐free (or equation‐free) method is designed for the efficient coarse‐grained computational study of complex problems . Sirisup et al presented a Galerkin‐free POD‐assisted method to simulate the incompressible Navier‐Stokes equations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, to address the above problems, we used a Galerkin‐free method to construct the POD‐ROM for flow in fractured porous media. The Galerkin‐free (or equation‐free) method is designed for the efficient coarse‐grained computational study of complex problems . Sirisup et al presented a Galerkin‐free POD‐assisted method to simulate the incompressible Navier‐Stokes equations.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that the Galerkin‐free ROM procedure is robust for large mesh deformations while maintaining high accuracy. Bergmann et al coupled a high‐fidelity simulation and a Galerkin‐free POD method for a zonal simulation of general flow fields. The obtained results from two test cases showed that the proposed approach could be applied to perform predictive simulations.…”
Section: Introductionmentioning
confidence: 99%
“…We use the initial condition u ( x ,0) = u 0 ( x ) and (for simplicity) homogeneous Dirichlet boundary conditions u ( x , t ) = 0 . ROMs have been used to reduce the computational cost of scientific and engineering applications that are governed by relatively few recurrent dominant spatial structures . In an off‐line stage, full‐order model (FOM) data on a given time interval are used to build the ROM.…”
Section: Introductionmentioning
confidence: 99%
“…ROMs have been used to reduce the computational cost of scientific and engineering applications that are governed by relatively few recurrent dominant spatial structures. [1][2][3][4][5][6][7][8][9][10][11][12] In an off-line stage, full-order model (FOM) data on a given time interval are used to build the ROM. In an online stage, ROMs are repeatedly used for parameter settings and/or time intervals that are different from those used to build them.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced Order Models have been extensively investigated as low cost prediction methods in several fields of engineering. As far as fluid mechanics is concerned there are several different approaches: Proper Orthogonal Decomposition (POD) [15,18,20,31,36,42,43,46,47,53], Proper Generalised Decomposition (PGD) [22], Reduced Basis (RB) [40,41], Dynamic Mode Decomposition [45], Grassmannian interpolation [4], Empirical Interpolation Method (EIM) [9], Discrete Empirical Interpolation Method (DEIM) [21], hyper-reduction [6,44,54], regularized ROM [52], domain decomposition approaches [8,13,16]. In this work the attention is focused on the use of POD for the prediction of compressible steady flows described by the Euler equations or by the Reynolds Averaged Navier-Stokes (RANS) equations.…”
Section: Introductionmentioning
confidence: 99%